#### Answer

See below

#### Work Step by Step

$$f(x)=x^4-x^3-5x^2-x-6=0\\x^4+2x^3-3x^3-6x^2+x^2+2x-3x-6=0\\x^3(x+2)-3x^2(x+2)+x(x+2)-3(x+2)=0\\(x+2)(x^3-3x^2+x-3)=0\\(x+2)(x-3)(x^2+1)=0$$
The solutions are $x+2=0\rightarrow x=-2\\x-3=0 \rightarrow x=3$

Chegg costs money, GradeSaver solutions are free!

Published by
McDougal Littell

ISBN 10:
0618595414

ISBN 13:
978-0-61859-541-9

See below

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.